Analysis of Self-Medication Knowledge about Gastritis Among Vocational School Students - Wardaniati, Isna; Nurhaliza, Siti; Pratiwi, Denia (JURNAL PROTEKSI KESEHATAN, 2023)
This study aims to analyze the level of knowledge on self-medication for gastritis among students at SMK Abdurrab and SMK Taruna Satria in Pekanbaru, Riau province, in 2023. Gastritis is a commonly self-treated condition, especially among adolescents, due to factors such as irregular eating patterns, unhealthy lifestyles, and increased activities. Proper self-medication can significantly contribute to national health maintenance, but irrational drug use can have negative consequences. Data was collected using consecutive sampling techniques with 171 respondents and a questionnaire as the research instrument. Data analysis employed descriptive analysis. The results indicated that the level of knowledge among SMK Abdurrab students regarding self-medication for gastritis was categorized as good for 57 respondents (68.7%) and fair for 26 respondents (31.3%). Meanwhile, SMK Taruna Satria students' knowledge levels were categorized as good for 24 respondents (27.3%), fair for 30 respondents (34.1%), and poor for 34 respondents (38.6%). A comparison of their knowledge levels in the good category showed that SMK Abdurrab students were 42% higher than SMK Taruna Satria students. In the fair category, SMK Taruna Satria students were 3% higher than SMK Abdurrab students, while in the poor category, it was only applicable to SMK Taruna Satria students at 39%.